2021
DOI: 10.3389/fmicb.2021.737616
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Transmitted Bacteria and Fungi Dominate Juvenile Plant Microbiomes

Abstract: Plant microbiomes play an important role in agricultural productivity, but there is still much to learn about their provenance, diversity, and organization. In order to study the role of vertical transmission in establishing the bacterial and fungal populations of juvenile plants, we used high-throughput sequencing to survey the microbiomes of seeds, spermospheres, rhizospheres, roots, and shoots of the monocot crops maize (B73), rice (Nipponbare), switchgrass (Alamo), Brachiaria decumbens, wheat, sugarcane, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 146 publications
(238 reference statements)
4
84
0
Order By: Relevance
“…Apart from Bacillus, the Actinobacterial Microbacterium and Curtobacterium were the prevalent genera (Table 2), as also reported for mature seeds of rice varieties cultivated in the Philippines and Japan [51,52]. The core microbiome of Bacillus and Microbacterium from seeds is consistent with our previous results from Dongxiang wild rice [35], and is supported by the recent finding that most seed transmitted bacteria are part of a core plant microbiome [17]. Some seed-borne pathogenic endophytes, such as Burkholderia spp.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Apart from Bacillus, the Actinobacterial Microbacterium and Curtobacterium were the prevalent genera (Table 2), as also reported for mature seeds of rice varieties cultivated in the Philippines and Japan [51,52]. The core microbiome of Bacillus and Microbacterium from seeds is consistent with our previous results from Dongxiang wild rice [35], and is supported by the recent finding that most seed transmitted bacteria are part of a core plant microbiome [17]. Some seed-borne pathogenic endophytes, such as Burkholderia spp.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies 2 of 15 have reported that seed microbes may originate from the earliest stages of seed development on the parent plant and then are able to establish early in soil grown seedlings [14,15]. Evidence has also indicated that vertical or seed transmission can significantly contribute to the plant microbiome [16,17]. Indeed, endophytic seed microbes have been previously shown to have potential to promote plant growth or control plant diseases [11,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…More work is needed to fully resolve the question of where nitrogenous chemicals detected around bacteria are actually fixed. As reported recently [ 38 ], many of these bacteria (including Pantoea , Pseudomonas , and Klebsiella ) appear to be taxonomically similar to a pan-angiosperm seed-transmitted microbiome with an otherwise poorly understood function within the plant. These bacteria are able to become internalized at meristems when leaf cells are forming.…”
Section: Discussionmentioning
confidence: 70%
“…Ample evidence over the past several decades suggests that all plants internalize microbes into their cells and tissues [ 13 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The obvious benefits to microbes are nutrients and protection when living inside the plant; plants also benefit from atmospheric nitrogen fixed by endophytic microbes [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. The mechanisms for the transfer of fixed nitrogen from bacteria to plant tissues are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been held for a long time that healthy plant tissues were sterile, the presence of complex communities of microorganisms inside every plant tissue has been proven [19,20]. These microorganisms, called endophytes, can have beneficial, neutral, or harmful effects on the host.…”
Section: Introductionmentioning
confidence: 99%